Black Tea Jelly Candy (Camellia Sinensis) to Increase Salivary Volume in Elderly: Preliminary Research - Lisa Prihastari; Rahma Anisa Sugiarto Putri; Ahmad Ronal (Denta Journal Kedokteran Gigi, 2024)
Background: Physiological changes in the elderly include decreased saliva production that causes dry mouth, difficulty in chewing and swallowing. Chewing gum and candies with a chewy texture like jelly can help stimulate the salivary glands. Black tea contains some phenolic and flavonoid compounds that have antioxidant properties that can increase the saliva flow rate. Objective: To determine the gap in saliva volume of elderly subjects before and after chewing black tea jelly candy compared to the saliva production when subjects chewed non-black tea candies and the control group (no treatment). This study also determined the prevalence of xerostomia in subjects. Materials and Methods: This field experiment was conducted using a Randomized Controlled Clinical Trials design with a pretest-posttest control group design. 30 elderly subjects aged 45-90 years in the Tresna Werda Budi Mulia 1 Nursing home, Jakarta were selected based on the predetermined inclusion criteria. They signed the informed consent and answered the Summated Xerostomia Inventory Questionnaire (SXI). Salivary volume before and after chewing black tea jelly candy was measured using a measuring cup. Statistical tests consisting of Oneway ANOVA and Dependent T-Test were performed to analyze the data. Results: The prevalence of elderly who complaining of xerostomia in this research was 40%. There was a significant gap in saliva volume between the three groups with p = 0.002 (P<0.05). An increase in saliva volume in the black tea jelly candy treatment group was identified. The average volume before intervention in the black tea jelly candy treatment group was 1.26 mL and after the intervention was 2.15 mL. Conclusion: Chewing black tea jelly candy increase the saliva volume in elderly subjects.